Experience with the Freestyle Valve: A Versatile Option. (9th April 2021) - Iqbal, Yassir Hassan; Senanayake, Eshan; Ashoub, Ahmed; Ranasinghe, Aaron; Pagano, Domenico; Rooney, Stephen; Bhabra, Moninder; Mascaro, Jorge
Abstract : Objective : The Medtronic Freestyle bioprosthesis is a stentless porcine aortic root. It provides a versatile implantation option either as a full root replacement or a sub-coronary aortic valve replacement. In this study we present our experience with the Freestyle valve in all circumstances over a 10-year period. Methods : All consecutive patients (n=70) undergoing Freestyle valve implantation either in the isolated or concomitant (n=9) setting were included between Jan 2009 to Jan 2020. A retrospective analysis of prospectively collected data was undertaken over 10 years. All case notes were reviewed (operation notes and follow up correspondence). Serial follow up echocardiography was reviewed to assess prosthesis function for structural valve deterioration. Echocardiography data was correlated with patient's clinical status during the follow up period. Mortality data was checked with national registries. Results : In-hospital mortality was 5.7% (n=4). Of the 66 patients, there were 6 deaths during follow up. Surviving patients were followed for a median period of 2 years (IQR 1-3 years). No patients underwent re-intervention for structural valve deterioration. At follow up, 90% patients' symptoms were consistent with NYHA class I-II and were successfully discharged to their primary care physician. Conclusions : Our experience with the Freestyle valve shows this to be a feasible bioprosthetic valve with good early and late outcomes. It is a versatile option both in the subcoronary position or as a complete aortic root replacement with low morbidity. Our experience has shown that the Freestyle valve is a preferable option in the setting of infective endocarditis with tissue destruction. Long-term follow-up has shown no structural valve deterioration in our experience, with good clinical outcomes. Freestyle valve used as aortic root versus subcoronary position Valve Position Root Replacement Subcoronary   35 35 Redo 18 16 Infective Endocarditis 12 19 Death (follow up) 3 3 Mean Bypass (Cross clamp) time/min 269 (185) 240 (156) Mean haemodynamic data MG- mmHg/PG-mmHg/AVA-cm2 6.6/12.5/1.6 6.0/8.0/0.7 Aortic regurgitation at follow up 0 0